Aspectos anatômicos, citogenéticos e palinológicos de espécies de Solanum - Cattelan, Letícia Vesz (2008)
The genus Solanum is considered the most complex of the Solanaceae family, presents great phenotipic variation. It possesses important economic crops such as potato, eggplant and scarlet eggplant used in the human feeding and tropical soda apple, important weed species that causes damage to commercial crops. The purpose of this work was to characterize two cultivated species of Solanum, eggplant (Solanum melongena L.) and scarlet eggplant (S. gilo L.), and a wild specie, tropical soda apple (S. viarum Dunal) based on the karyotype and in reproductive and anatomical aspects. In eggplant the presence of simple and captate glandular trichomes was observed, in scarlet eggplant and tropical soda apple simple, captate glandular and star trichomes was observed with different numbers of arms, demonstrating different properties of environmental adaptation between cultivated and wild species. The total length of each chromosome of eggplant, scarlet eggplant and tropical soda apple had varied between 1.44 - 4.15 µm, 2.04 - 4.24 µm and 2.41 - 5.06 µm, respectively. The meiosis was regular, with 12 normal bivalents. The pollen of the three species are 3-colporate and they were classified as prolate spheroidal, presenting different thickness of the exine.